The Effectiveness of the Self-Protection Model on Children’s Assertive Behavior In Sexual Violence - Amnestito, Zafhira Alayda; Jati, Sri Nugroho; Vidyastuti (Nusantara Journal of Behavioral and Social Science, 2024)
Children are particularly vulnerable to sexual violence because they are considered weak or powerless. Research data has found that 20% to 33% of girls and 10% to 16% of boys will become victims of sexual abuse before the age of 18. Kubu Raya Regency recorded that in 2021, there were 74 cases of violence against children and adolescents, which is quite high, with the majority of cases being sexual violence experienced by children aged 6-12 years. This indicates that children need to learn self-protection efforts through the Self-Protection Model. The Self-Protection Model is an intervention model provided as an effort to address the issue of sexual violence against children. This study employs a quantitative experimental design. The study uses purposive sampling, targeting children aged 9-12 years; attending elementary school; and willing and permitted by the school to participate until the intervention sessions are completed, with a total of 10 boys and 10 girls. Data analysis shows a difference in the application of the Self-Protection Model. The results of the Wilcoxon test output "Test Statistics" indicate that the Asymp.Sig. (2-tailed) value is 0.000. Since the value of 0.000 less than 0.05, it can be concluded that Ha is accepted. This means there is a significant difference in assertive behavior between the pretest and posttest results, suggesting that the Self-Protection Model has an influence on children as a method of self-protection against sexual abuse. Abstrak: Anak-anak rentan terhadap kekerasan seksual karena dianggap lemah atau tidak berdaya. Data penelitian menunjukkan bahwa 20% hingga 33% anak perempuan dan 10% hingga 16% anak laki-laki akan menjadi korban kekerasan seksual sebelum usia 18 tahun. Di Kabupaten Kubu Raya tercatat pada tahun 2021 terdapat 74 kasus kekerasan terhadap anak dan remaja, dengan mayoritas kasus berupa kekerasan seksual yang dialami oleh anak-anak usia 6-12 tahun. Ini menunjukkan bahwa anak-anak perlu mempelajari upaya perlindungan diri melalui Self-Protection Model. Model ini adalah model intervensi yang diberikan sebagai upaya untuk mengatasi masalah kekerasan seksual terhadap anak. Penelitian ini menggunakan desain eksperimen kuantitatif dengan sampel purposif, menargetkan anak-anak berusia 9-12 tahun, bersekolah di SD, dan bersedia serta diizinkan oleh pihak sekolah untuk berpartisipasi hingga sesi intervensi selesai. Sebanyak 10 anak laki-laki dan 10 anak perempuan berpartisipasi dalam penelitian ini. Analisis data menunjukkan perbedaan dalam penerapan Self-Protection Model. Hasil dari uji Wilcoxon output “Test Statistcs”, diketahui Asymp.Sig. (2-tailed) bernilai 0,000. Karena nilai 0,000 kurang dari 0,05 maka dapat disimpulkan bahwa Ha diterima. Artinya ada perbedaan antara hasil perilaku asertif untuk pretest dan posttest, sehingga dapat disimpulkan bahwa ada pengaruh dari Self-Protection Model terhadap anak sebagai upaya perlindungan diri dari kekerasan seksual.